Lessons learned in delayed identification of a misplaced electrode array in the vestibule - Huey Ting Diong; Yuhan Wong; Shermaine Png; Yeow Seng Raymond Ngo (Journal of Otology)
To report a case of cochlear implantation with a misplaced electrode array in the vestibule and the causes for the delay in identification. A 23-year-old male with left single-sided deafness underwent cochlear implantation. The intraoperative assessment did not reveal any major red flags of electrode array misplacement. He did not display any vestibular symptoms postoperatively but showed poor speech performance, even though the aided tone audiometry revealed good sound detection thresholds. High-resolution computed tomography (HRCT) showed that the entire perimodiolar electrode array was situated within the vestibule, and a revision surgery was conducted. Retrospective analysis of the neural response telemetry (NRT) revealed subtle differences in responses between the misplaced and correctly placed electrode arrays. Unlike previously reported cases, the patient did not display vestibular symptoms despite the misplacement of the electrode in the vestibule due to existing weakness in otolithic function. Further investigation is warranted when a motivated patient with normal inner ear anatomy does not show benefit with the cochlear implant post-operatively.